Fluorescence Spectroscopy Study on the Interaction between Evodiamine and Bovine Serum Albumin - Mingxiong Tan; Weijiang Liang; Xujian Luo; Yunqiong Gu (Journal of Chemistry)
The interaction of evodiamine (Evo) with bovine serum albumins (BSAs) at different two temperatures (298 and 310 K) was investigated by means of fluorescence spectroscopy. The experimental results showed that Evo binds with BSA via a static quenching procedure with association constants K of 1.61×106 L/mol at 298 K and 6.78×105 L/mol at 310 K. The number of bound Evo molecules per protein is 1.31 at 298 K and 1.33 at 310 K. The results suggested that Evo reacts with BSA chiefly through hydrophobic and electrostatic interactions, and it does not alter the α-helical nature of BAS.